Radicular Cyst With Actinomycotic Infection in an Upper Anterior Tooth - Shuei-Kuen Tseng (Journal of the Formosan Medical Association, 2009)
Actinomycosis is an infection caused by filamentous, branching, Gram-positive anaerobic bacteria. It rarely infects the jawbone. This case report describes a patient with a left maxillary central incisor with an apical lesion and actinomycotic infection. A 23-year-old male patient underwent conventional root canal treatment of tooth 21, in a local dental clinic for about 1 year. However, percussion pain and a sinus tract that originated from tooth 21 were still present after treatment. Nonsurgical root canal treatment of tooth 21 was performed again but failed to relieve the symptoms. Therefore, apicoectomy and retrograde filling of the apical root canal with mineral trioxide aggregate were carried out. Periradicular bony defect was grafted by biocompatible material, and postoperative antibiotics (250 mg amoxicillin) were given three times daily for 5 days. Pathological examination of the removed periapical tissue showed a radicular cyst with actinomycosis. At the 9-month postoperative recall, the sinus tract had disappeared and radiographic examination showed healing of the apical lesion. Periradicular actinomycosis is one important reason for failure of nonsurgical endodontic treatment. Clinically, if the tooth shows a recurrent sinus tract and poor response to conventional root canal treatment combined with antibiotic control, apical actinomycotic infection should be highly suspected, and an alternative endodontic surgical approach is needed for successful treatment.